Validation of a care pathway for the use of faecal calprotectin in monitoring patients with Crohn's disease. Issue 3 (30th January 2017) - Turvill, James; Rook, Lisa; Rawle, Maxine; Robins, Gerry; Smale, Simon; Kant, Prashant; Phillips, Anne
Abstract : Introduction: We have previously published an evidence-based care pathway for the use of faecal calprotectin (FC) to monitor patients with Crohn's disease established on therapy. Patients are treated as low, intermediate or high risk of continuing Crohn's disease activity based on their FC, whatever their phenotype and surgical status are. Low-risk patients (FC <100 µg/g) are offered 12 monthly follow-ups or step down of therapy if asymptomatic or initial expectant symptomatic treatment. Intermediate-risk patients (FC 100–250 µg/g) are reviewed at 6 months with a repeat FC. High-risk patients (two consecutive FCs >250 µg/g) are flagged up to the responsible clinician as likely having an active Crohn's disease. Methods: To validate this care pathway over a 2-year period, by determining its negative predictive value (NPV) and positive predictive value (PPV). Results: 123 patients were managed by means of the care pathway for a mean of 24.4 months. The NPV and PPV were 0.97 (CI 0.93 to 0.98) and 0.85 (CI 0.80 to 0.94), respectively (sensitivity: 0.92 (0.83 to 0.96) and specificity: 0.95 (0.92 to 0.98)). Importantly 69% of patients with FC >250 µg/g were in clinical remission, the care pathway identifying patients who would benefit from presymptomatic disease modification. Conclusions: This validation of a pragmatic clinical care pathway demonstrates a safe and effective mechanism by which to use FC to monitor risk of disease activity in patients with Crohn's disease established on therapy. It provides a framework for prioritising follow-up and for identifying patients at risk of continuing disease activity or those in whom therapy could be stepped down.